Extremophiles in a changing world - D. A. Cowan; S. V. Albers; G. Antranikian; H. Atomi; B. Averhoff; M. Basen; A. J. M. Driessen; M. Jebbar; Z. Kelman; M. Kerou; J. Littlechild; V. Müller; et al. (Extremophiles, 2024)
Extremophiles and their products have been a major focus of research interest for over 40 years. Through this period, studies of these organisms have contributed hugely to many aspects of the fundamental and applied sciences, and to wider and more philosophical issues such as the origins of life and astrobiology. Our understanding of the cellular adaptations to extreme conditions (such as acid, temperature, pressure and more), of the mechanisms underpinning the stability of macromolecules, and of the subtleties, complexities and limits of fundamental biochemical processes has been informed by research on extremophiles. Extremophiles have also contributed numerous products and processes to the many fields of biotechnology, from diagnostics to bioremediation. Yet, after 40 years of dedicated research, there remains much to be discovered in this field. Fortunately, extremophiles remain an active and vibrant area of research. In the third decade of the twenty-first century, with decreasing global resources and a steadily increasing human population, the world’s attention has turned with increasing urgency to issues of sustainability. These global concerns were encapsulated and formalized by the United Nations with the adoption of the 2030 Agenda for Sustainable Development and the presentation of the seventeen Sustainable Development Goals (SDGs) in 2015. In the run-up to 2030, we consider the contributions that extremophiles have made, and will in the future make, to the SDGs.

Enhancing the utilization of healthy living interventions among cancer survivors in historically underserved populations and communities - Margaret Raber; Ruth Rechis; Denise M. LaRue; Thy T. Ho-Pham; Katherine Oestman; Michael T. Walsh; Darya Kizub; Hilary Ma; Esperanza Galvan; Hui Zhao; Jennifer Gonzalez; Xiudong Lei; et al. (Cancer Causes & Control, 2023)

Health Literacy Interventions in Cancer: a Systematic Review - A. J. Housten; C. M. Gunn; M. K. Paasche-Orlow; K. M. Basen-Engquist (Journal of Cancer Education, 2021)

Energy balance related lifestyle factors and risk of endometrial and colorectal cancer among individuals with lynch syndrome: a systematic review - Adriana M. Coletta; Susan K. Peterson; Leticia A. Gatus; Kate J. Krause; Susan M. Schembre; Susan C. Gilchrist; Mala Pande; Eduardo Vilar; Y. Nancy You; Miguel A. Rodriguez-Bigas; Larkin L. Strong; Patrick M. Lynch; et al. (Familial Cancer, 2019)